Analgesic efficacy and safety of four different anesthesia/postoperative analgesia protocols in patients following total hip arthroplasty - Kendrišić, Mirjana L; Šurbatović, Maja; Djordjević, Dragan; Trifunović, Bratislav; Jevdjić, Jasna (Vojnosanitetski pregled, 2017)
Background/Aim. Hip replacement surgery can initiate significant postoperative pain caused by bone alterations, implant, and soft tissue or nerve injuries. Postoperative analgesia using regional techniques has been shown to have numerous advantages over the intravenous use of morphine. However, numerous side effects and complications of postoperative continuous epidural analgesia have been reported recently. The aim of this prospective, randomized study was to investigate whether continuous lumbar plexus block can be a safe and efficacious alternative for postoperative analgesia in comparison with epidural analgesia and patient-controlled analgesia with morphine (PCA morphine) for hip arthroplasty. Methods. This prospective study included 60 patients, scheduled for total hip arthroplasty. Patients were randomized into 4 groups: the group central nerve block – epidural (CNB), the group peripheral nerve block – lumbar plexus block (PNB), the group spinal anesthesia-PCA morphine (SAM) and the group general anesthesia-PCA morphine (GAM). The quality of analgesia and side effects (hypotension, nausea, vomiting, urinary retention) were recorded in all groups at 4 h, 12 h, and 24 h after surgery. Pain scores were assessed using Visual Analogue Scale (VAS), both at rest and on moving. Results. Our findings demonstrated that the use of a continuous lumbar plexus block provides effective analgesia at rest and on moving, during 24 h after hip arthroplasty. Pain scores varied significantly among the groups 4 h postoperatively (F = 21.827; p < 0.01), 12 h postoperatively (F = 41.925; p < 0.01) and 24 h postoperatively (F = 33.768; p < 0.01) with the highest scores ≥ 3 in the GAM group. Patients from the PNB group had satisfactory analgesia, comparable with patients from the CNB group. The incidence of nausea was significantly lower in the PNB group 12 h after the operation (χ2 = 9.712; p < 0.01). The incidence of urine retention was significantly different 12 h after the operation, with a presence only in the CNB group, with the incidence of 33.3% (χ2 = 16.365; p < 0.01). In all studied groups, the incidence of hypotension was not significantly different postoperatively. Conclusion. Administration of postoperative analgesia using continuous lumbar plexus block produces satisfactory analgesia with a low incidence of side effects when compared to epidural analgesia or parenteral opioids following hip arthroplasty.